Rediscovering apprenticeship : research findings of the International Network on Innovative Apprenticeship (INAP) - Rauner, Felix [Herausgeber]; Smith, Erica [Herausgeber] (Springer Science + Business Media, 2010)
"The rediscovery of the value of apprenticeships has been one of the most significant trends in vocational education in recent years, and has prompted an array of research and development projects in countries around the world. In this volume, the renewed interest in the apprenticeship tradition and the various steps towards the implementation of innovative apprenticeship programmes are analysed and discussed from different perspectives. Beginning with a number of chapters that describe recent developments in apprenticeship training in different national contexts, the book moves on to analyze the way in which both the quality and profitability of apprenticeship act in concert as the most influential drivers of innovation in this field." (Verlag, BIBB-Doku)
Keywords: T 1.5 International vergleichende Berufsbildungsforschung; Berufsbildungsforschung; Berufsausbildung; Kompetenzerwerb; Lernen am Arbeitsplatz; Kosten-Nutzen-Analyse; Internationaler Vergleich